Variation of blubber thickness for three marine mammal species in the southern Baltic Sea - Siebert, Ursula; Grilo, Miguel L.; Kesselring, Tina; Lehnert, Kristina; Ronnenberg, Katrin; Pawliczka, Iwona; Galatius, Anders; Kyhn, Line A.; Dähne, Michael; Gilles, Anita (Frontiers in Physiology, 2022)
Evaluating populational trends of health condition has become an important topic for marine mammal populations under the Marine Strategy Framework Directive (MSFD). In the Baltic Sea, under the recommendation of Helsinki Commission (HELCOM), efforts have been undertaken to use blubber thickness as an indicator of energy reserves in marine mammals. Current values lack geographical representation from the entire Baltic Sea area and a large dataset is only available for grey seals (Halichoerus grypus) from Sweden and Finland. Knowledge on variation of blubber thickness related to geography throughout the Baltic Sea is important for its usage as an indicator. Such evaluation can provide important information about the energy reserves, and hence, food availability. It is expected that methodological standardization under HELCOM should include relevant datasets with good geographical coverage that can also account for natural variability in the resident marine mammal populations. In this study, seasonal and temporal trends of blubber thickness were evaluated for three marine mammal species—harbor seal (Phoca vitulina), grey seal (Halichoerus grypus) and harbor porpoise (Phocoena phocoena)—resident in the southern Baltic Sea collected and investigated under stranding networks. Additionally, the effects of age, season and sex were analyzed. Seasonal variation of blubber thickness was evident for all species, with harbor seals presenting more pronounced effects in adults and grey seals and harbor porpoises presenting more pronounced effects in juveniles. For harbor seals and porpoises, fluctuations were present over the years included in the analysis. In the seal species, blubber thickness values were generally higher in males. In harbor seals and porpoises, blubber thickness values differed between the age classes: while adult harbor seals displayed thicker blubber layers than juveniles, the opposite was observed for harbor porpoises. Furthermore, while an important initial screening tool, blubber thickness assessment cannot be considered a valid methodology for overall health assessment in marine mammals and should be complemented with data on specific health parameters developed for each species.